Exploring the Moderating Role of Organizational Justice in the Relationship Between Work Stress and Burnout Among Nurses: A JD-R Framework Approach - Meiffa Herfianti; Lizar Alfansi; Slamet Widodo; Fahrudin JS Pareke (Yayasan Bina Bisnis Nusantara Medan, 2025)
Work stress and burnout among nurses have become critical issues in human resource management, particularly in the aftermath of the COVID-19 pandemic. This study develops a conceptual model exploring how organizational justice moderates the relationship between work stress and burnout, based on the Job Demands–Resources (JD-R) framework. Using a quantitative approach with 315 respondents selected through proportional random sampling, data were analyzed using Partial Least Squares (PLS) with SmartPLS software. The results show that job stress significantly and positively affects burnout (p < 0.001). Job resources significantly reduce job stress (p < 0.05) and act as a mediator, decreasing burnout through the job stress pathway (p < 0.05). However, job demands were positively related to burnout, but this relationship was not significant (p > 0.05), leading to the rejection of this hypothesis. Organizational justice significantly reduces job stress (p < 0.05), moderating the relationship between job stress and burnout. Specifically, higher perceptions of organizational justice weaken the effect of job stress on burnout. These findings emphasize the importance of organizational justice and job resources in managing work stress and preventing burnout. The results highlight the need for healthcare organizations to integrate justice principles into their practices to mitigate burnout and enhance employee well-being